Ethical and Legal Issues of Presumed Consent - Kumar, M S Vinay; Valsangkar , Sameer (Journal of Indian Academy of Forensic Medicine, 2015)
In India shortage of organ donors is a major health problem with ethical and legal concerns and  requires immediate attention. Ever since the first transplants were carried out in the 1950s, there has  been an imbalance between the availability of donated organs and the number of recipients. The  objective of this article is to address various ethical and legal aspects of presumed consent. Presumed  consent takes the onus away from the individual to register in order to become organ donor. Instead the individual must sign a register during his life if he is unwilling to donate. The argument which strongly  favours this policy is thousands of healthy organs are destroyed every hour due to burial and cremation  whereas innumerable people are dying because of want of these organs. The other side of this argument  is organ donation should be the choice of the individual and must not be forced. Before passing  legislation on presumed consent ethical and legal issues of presumed consent should be addressed and  it is better to implement lesser ethically and legally debatable methods to overcome the backlog of organ  donors than to introduce law on presumed consent.
Keywords: Organ donors; Presumed Consent; Ethical/Legal issues